No maps for these territories: exploring philosophy of memory through photography - Kirby, Alun (Estudios de Filosofía, 2021)
I begin by examining perception of photographs from two directions: what we think photographs are, and the aspects of mind involved when viewing photographs. Traditional photographs are shown to be mnemonic tools, and memory identified as a key part of the process by which photographs are fully perceived. Second, I describe the metamorphogram; a non-traditional photograph which fits specific, author-defined criteria for being memory. The metamorphogram is shown to be analogous to a composite of all an individual’s episodic memories. Finally, using the metamorphogram in artistic works suggests a bi-directional relationship between individual autobiographical memory and shared cultural memory. A model of this relationship fails to align with existing definitions of cultural memory, and may represent a new form: sociobiographical memory. I propose that the experiences documented here make the case for promoting a mutually beneficial relationship between philosophy and other creative disciplines, including photography.